Spatial and temporal pattern of sympatric fish assemblage in the Al-Sweib River South of Iraq - Abdullah, Abdul Hussein Jaafer; Abdullah, Sajad Abdul-Geni; Al- Robayii, Osama Abid Alhadi (Journal of Kerbala for Agricultural Sciences, 2018)
Spatial and temporal pattern of fish assemblages in the Al-Sweib River Southern Iraq was investigated from January to December 2017 to determine the nature of the fish community structure in the river. Two stations were chosen for the implementation of the work. Monthly variations in rates of water temperature were measured; it has been ranged from 11°C in December to 36°C in July and August. Salinity rates differ from 0.81ppt in February to 1.66 ppt in August. The value rates of dissolved oxygen in the studying area varied from 6.7 mg/l in August to 9.9 mg/l in January. The total alkalinity values rates in the work area differ from 115 mg/l in February to 156 mg/l in August. Several fishing methods were used to collect the samples of fishes: drift and fixed gill net, seine net and cast net. A total of 6902 fish individuals collected from the Al-Sweib River included 27 species, represented 27 genera and 12 families, all of them belonging to Osteichthyes. The species were 11 native, ten alien and six marine. Four species topped the total numerical relative abundance in present the investigated area, formed 81.72% of the total number, Planiliza abu 35.34%, Oreochromis aureus 18.68%, Carassius gibelio 17.51% and Coptodon zillii 10.19%. The diversity index values classified as poor in the studying area, the values ranged from 1.48 in December to 2.07 in March at station 1, whereas station 2 from 1.33 in December to 2.17 in May. Values of richness index were between turbulent to half integrate, they ranged from 1.33 in December to 2.31 March in station1, while from 1.50 in November to 2.78 in June station 2. Evenness index between half balanced to balance varied from 0.65 in October and 0.89 in August station 1, but at station 2 it was between 0.56 in December and 0.87 in July. The total similarities between the stations formed 36.84% in June and 72.73% in November. The study showed that the composition of fish community in Al-Sweib River was similar to that of the northern part of Shatt Al-Arab River.